Revealed Notions of Distributive Justice I – Theory - Nicole Becker; Kirsten Häger; Jan Heufer (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
We provide a framework to decompose preferences into a notion of distributive justice and a selfishness part and to recover individual notions of distributive justice from data collected in appropriately designed experiments. 'Dictator games' with varying transfer rates used in Andreoni and Miller (2002) and Fisman et al. (2007) can be used to assess individuals' preferences, but - with the help of simple new axioms - also to recover some part of individuals' notion of justice. 'Social planner' experiments or experiments under a 'veil of ignorance' (Rawls 1971) can be used to recover larger parts of the notion of justice. The axioms also allow a simple test for the validity of such an experimental approach, which is not necessarily incentivecompatible, and to recover a greater part of an individual's preference relation in dictator experiments than before. Interpersonal comparison of the individual intensity of justice (or fairness) similar to the suggestions in Karni and Safra (2002b) are possible, and we can evaluate the intensity based on an individual's own notion of justice. The approach is kept completely non-parametric. As such, this article is in the spirit of Varian (1982) and Karni and Safra (2002a). – – Der Artikel stellt einen Ansatz vor, mit dem Präferenzen in eine Gerechtigkeits- und Eigennutzkomponente zerlegt werden können, und mit dem individuelle Vorstellungen von Verteilungsgerechtigkeit mit experimentellen Methoden erfasst werden können. "Diktatorspiele" mit unterschiedlichen Transferraten, die bei Andreoni und Miller (2002) und Fisman et al. (2007) verwendet wurden, können die individuellen Präferenzen erfassen, aber - mit der Hilfe von einfachen neuen Axiomen - auch einen Teil der Gerechtigkeitsvorstellung. "Soziale Planer"-Experimente oder Experimente unter einem "Schleier der Ignoranz" (Rawls 1971) können größere Teile der Gerechtigkeitsvorstellung erfassen. Die Axiome ermöglichen auch einfache Tests für die Validität dieses nicht notwendigerweise anreizkompatiblen experimentellen Ansatzes. Der Ansatz ist komplett nichtparametrisch und in dieser Hinsicht im Sinne Varians (1982) und Karni und Safra (2002a). Interpersonelle Vergleiche der Intensität des Sinnes für Gerechtigkeit, ähnlich zum Ansatz bei Karni und Safra (2002b) sind möglich, und wir können die Intensität basierend auf individuellen Gerechtigkeitsvorstellungen bewerten.
Keywords: C14; C91; D11; D12; D63; D64; 330; altruism; distributive justice; nonparametric analysis; preference decomposition; revealed preference; social preferences